DAYA SAING EKSPOR CENGKEH INDONESIA DI PASAR GLOBAL - Fadhlan Zuhdi; Khoiru Rizqy Rambe (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
Increasing clove export market share in global markets has promising potential. The aims of this study are to identify the market structure of clove exporting countries and to measure the level of competitiveness and competitive advantage possessed by each exporting country. This study used time series data of Indonesian, Madagascar, Singapore and Comoro clove exports since 2001-2019. The CR4 method is used to identify the market structure, Revealed Comparative Advantage (RCA) used to measure the level of export competitiveness comparatively and Export Competitiveness Index (ECI) used to identify the competitive advantage of each exporting country. The results of the study stated that the market structure formed leads to an oligopoly market with Indonesia and Madagascar as market leaders.  Meanwhile, the level of export competitiveness and competitive advantage possessed by Indonesia tend to increase. To increase the share of Indonesian clove exports can be done by conducting dissemination to clove farmers about cultivation technology. So, the farmers can produce high quality clove.